Employee Performance In The Regional Office Of The National Land Agency Of Bengkulu Province - Imanda, Antonio; Yusuarsono, Yusuarsono; Sapruzi, Gaul (Journal of Research in Social Science and Humanities, 2022)
This study aims to evaluate employee competencies and their impact on performance at the Regional Office of the National Land Agency of Bengkulu Province. A descriptive qualitative approach was employed, with data collected through observations, structured interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The results indicate that the five indicators of competency—motivation, character, self-concept, knowledge, and skills—have been fulfilled and significantly contribute to employee performance. Employees demonstrate high work motivation, professional character, positive self-concept, strong technical knowledge, and relevant administrative and technical skills. The limitation of this study lies in its narrow scope, focusing on a single regional agency with a limited number of informants. This research contributes to the development of human resource management policies in the public sector, especially in designing competency-based training programs and holistic performance evaluation systems.